Pengembangan Bahan Ajar IPA Terpadu Berbasis Kearifan Lokal di Lahan Basah dengan Menggunakan Model Guided Inquiry di SMP - noor aida (Indonesian Journal of Natural Science Education, 2020)
This research is motivated by the fact that the learning of natural science in general has not been related to contextual learning resources. One of the learning resources in the form of integrated natural science teaching materials is still not connected to the wetlands or local wisdom of the local community. Therefore, a local wisdom based integrated science teaching material development study was carried out on wetlands using the guided inquiry model. This study aims to determine the validity, practicality, effectiveness of teaching materials, and skills of science process of students. Included in the type of research and development using the Tessmer model. Students of class VII-E of SMP Negeri 15 Banjarmasin as a trial subject. Data is generated through sheets from validators, questionnaire responses from students, learning outcomes, and observation sheets of students' scientific process skills. Data were analyzed by quantitative and qualitative descriptive. The results of the study show that: (1) the validity of teaching materials is valid, (2) the practicality of teaching materials has practical criteria, (3) the effectiveness of teaching materials is effective, and (4) the science process skills of students are very good. Based on the results of the study, it was concluded that the integrated science based learning material based on local wisdom in wetlands using the guided inquiry model in junior high school was appropriate for use during the learning process.